Political Ideology, Public Policy and Human Development in India: Explaining the Gap Between Gujarat and Tamil Nadu - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2015)
Four decades ago the Indian states of Gujarat and Tamil Nadu had identical scores on the human development index. Both states have since experienced similar rates of economic growth and Gujarat has received more foreign investment, but Tamil Nadu has witnessed much stronger advances in human development. What explains this divergence? Through comparative historical, statistical and public policy analysis and interviews, we conclude that the implementation of government policies as a manifestation of political ideology and the quality of public administration have played a defining role in explaining Gujarat's more lopsided and Tamil Nadu's more balanced human development trajectories. Our findings suggest that a more egalitarian ideology and higher quality of public administration have been crucial to Tamil Nadu's success in simultaneously improving human and economic development.